2006
DOI: 10.1080/08957950600881512
|View full text |Cite
|
Sign up to set email alerts
|

In situstudy of magmatic processes: a new experimental approach

Abstract: -We present an internally heated autoclave, modified in order to allow in situ studies at pressure up to 0.5 GPa and temperature up to 1000°C. It is equipped with transparent sapphire windows, allowing the observation of the whole experiment along the horizontal axis. In the experimental cell the sample is held between two thick transparent plates of sapphire or diamond, placed in the furnace cylinder. The experimental volume is about 0.01 cm 3 . Video records are made during the whole experiment.This tool is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…These studies investigated bubble growth in 78 rhyolitic melts and showed experimental results consistent with the growth laws 79 inferred by theoretical models (Toramaru 1989;Toramaru 1995;Proussevitch et al 80 1993; Lyakhovsky et al 1996). More recently, high-pressure devices were developed 81 and used to investigate in-situ bubble growth in silicic melts (Martel and Bureau 82 2001; Gondé et al 2006; Gondé et al 2011). The experimental results were also 83 consistent with observations of natural products, demonstrating the reliability of the The low experimental temperature (generally well below 1000 °C) and the 86 exclusive use of rhyolitic-type melt compositions are the main limitations of the 87 experiments carried out so far.…”
Section: Introduction 52mentioning
confidence: 79%
“…These studies investigated bubble growth in 78 rhyolitic melts and showed experimental results consistent with the growth laws 79 inferred by theoretical models (Toramaru 1989;Toramaru 1995;Proussevitch et al 80 1993; Lyakhovsky et al 1996). More recently, high-pressure devices were developed 81 and used to investigate in-situ bubble growth in silicic melts (Martel and Bureau 82 2001; Gondé et al 2006; Gondé et al 2011). The experimental results were also 83 consistent with observations of natural products, demonstrating the reliability of the The low experimental temperature (generally well below 1000 °C) and the 86 exclusive use of rhyolitic-type melt compositions are the main limitations of the 87 experiments carried out so far.…”
Section: Introduction 52mentioning
confidence: 79%
“…In order to examine the first seconds of bubble formation, we employed 4D X-ray tomographic microscopy as a tool to image and record nucleation and growth, therefore building on the pioneering work on in situ 2D observations of bubble nucleation and growth (Bagdassarov et al, 1996;Gondé et al, 2006Gondé et al, , 2011Applegarth et al, 2013;Masotta et al, 2014) with the latest developments in 3D and 4D imaging of geological materials (Bai et al, 2008;Baker et al, 2012aBaker et al, , 2012bPistone et al, 2015aPistone et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Although this technique was successfully employed, especially for the study of metastable phases, no investigations were conducted to explore textural development in polycrystalline aggregates. Gondé et al (2006) developed a sapphire-windowed, internally heated pressure vessel that allows the in situ observation of magmatic processes at pressures up to 0.5 GPa and temperatures up to 1000 °C.…”
Section: Introductionmentioning
confidence: 99%